Du Mingxin’s Musical Legacy: National Identity Through the Red Detachment of Women - Wang, Zhen; Rodsakan, Tepika; Jamnongsarn, Surasak (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: Du Mingxin’s The Red Detachment of Women merges Chinese revolutionary themes with Western compositional techniques, offering a distinctive model for expressing national identity through music. By analyzing the piano suite adaptation of the ballet, this study explores how Du’s compositions serve as both artistic representations of Chinese cultural memory and influential contributions to the modernization of Chinese piano music. Materials and Methods: A qualitative approach was adopted, integrating literature review, historical investigation, music ontology analysis, and expert interviews. This comprehensive methodology enables a detailed evaluation of stylistic traits, thematic content, and national identity construction within Du Mingxin’s works. Results: Findings reveal that Du’s music effectively blends folk-based melodic materials, pentatonic modes, and ethnic timbral imitations with modern compositional frameworks. The Red Detachment of Women stands as a cultural symbol, embodying revolutionary history, regional heritage, and collective memory. Its artistic and educational significance has contributed to the shaping of national identity and cultural resilience in both domestic and international contexts. Conclusion: Du Mingxin’s compositions exemplify the fusion of Chinese and Western music, reinforcing ethnic identity through innovation and cultural preservation. His works extend beyond musical aesthetics to function as pedagogical tools and national narratives. This research highlights the enduring relevance of Du’s music in fostering cultural confidence and advancing Chinese music in the global arena.